2007
DOI: 10.1016/j.cell.2007.03.047
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor Suppressor PP2A Aβ Regulates the RalA GTPase

Abstract: The serine-threonine protein phosphatase 2A (PP2A) is a heterotrimeric enzyme family that regulates numerous signaling pathways. Biallelic mutations of the structural PP2A Abeta subunit occur in several types of human tumors; however, the functional consequences of these cancer-associated PP2A Abeta mutations in cell transformation remain undefined. Here we show that suppression of PP2A Abeta expression permits immortalized human cells to achieve a tumorigenic state. Cancer-associated Abeta mutants fail to rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
186
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(194 citation statements)
references
References 57 publications
8
186
0
Order By: Relevance
“…These biochemical data can be explained in light of recent structural findings: Glu64 forms a hydrogen bond with the Ca C terminus, thereby stabilizing the A-PR61/B 0 g1 interface [36,37] (see Box 1, Figure Ib), Arg418 maps to the A-C interface and forms a hydrogen bond with Glu67 of Ca [34,36]. In addition, partial knockdown of the Aa subunit results in selective loss of PP2A holoenzymes containing the PR61/B 0 g subunit [29,30], rendering cells tumorigenic via increased Ser62 phosphorylation and stabilization of c-Myc [5,29,30]. The overexpression of Aa harboring cancerderived mutations cannot rescue this phenotype [29].…”
Section: Reviewmentioning
confidence: 65%
See 2 more Smart Citations
“…These biochemical data can be explained in light of recent structural findings: Glu64 forms a hydrogen bond with the Ca C terminus, thereby stabilizing the A-PR61/B 0 g1 interface [36,37] (see Box 1, Figure Ib), Arg418 maps to the A-C interface and forms a hydrogen bond with Glu67 of Ca [34,36]. In addition, partial knockdown of the Aa subunit results in selective loss of PP2A holoenzymes containing the PR61/B 0 g subunit [29,30], rendering cells tumorigenic via increased Ser62 phosphorylation and stabilization of c-Myc [5,29,30]. The overexpression of Aa harboring cancerderived mutations cannot rescue this phenotype [29].…”
Section: Reviewmentioning
confidence: 65%
“…Similar to Aa, Ab subunits harboring cancer-derived mutations display diminished capacity to bind to the C-or specific B-type subunits [30,39] and fail to rescue the transformed phenotype of cells caused by reduced Ab levels [30]. Aa expression also fails to revert the Abdependent phenotype, indicating that Aa and Ab prevent cell transformation via distinct mechanisms.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of BTG4 is a common event in chronic lymphocytic leukaemia, and epigenetic silencing of BTG4 by CpG island methylation occurs in colorectal cancer (Auer et al 2005, Toyota et al 2008. PPP2R1B regulates RaIA GTPase and inhibits cell growth (Sablina et al 2007). Inactivation of PPP2R1B by downregulation, or mutation, has been demonstrated in B-cell chronic lymphocytic leukaemia, lung cancer and colon cancer (Wang et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, we and others have determined that Ral growth regulatory activities are regulated by phosphorylation. Hahn and colleagues showed that serine-threonine protein phosphatase 2A dephosphorylation of RalA at S183 and S194 abolished RalA transforming activity (8). Two other studies determined that S194 could be phosphorylated by Aurora A and that this phosphorylation was essential for RalA transforming activity (9) and RalA-dependent PDAC anchorage-independent and tumorigenic growth (10).…”
Section: Introductionmentioning
confidence: 99%